Detection of quinoline in G. boninense-infected plants using functionalized multi-walled carbon nanotubes: a field study - Akanbi, Fowotade Sulayman; Yusof, Nor Azah; Abdullah, Jaafar; Sulaiman, Yusran; Hushiarian, Roozbeh (Multidisciplinary Digital Publishing Institute, 2017)
Carbon nanotubes (CNTs) reinforced with gold nanoparticles (AuNPs) and chitosan nanoparticles (CTSNPs) were anchored on a screen-printed electrode to fabricate a multi-walled structure for the detection of quinoline. The surface morphology of the nanocomposites and the modified electrode was examined by an ultra-high resolution field emission scanning electron microscope (FESEM), and Fourier-transform infrared (FT-IR) spectroscopy was used to confirm the presence of specific functional groups on the multi-walled carbon nanotubes MWCNTs. Cyclic voltammetry (CV) and linear sweep voltammetry (LSV) were used to monitor the layer-by-layer assembly of ultra-thin films of nanocomposites on the surface of the electrode and other electrochemical characterizations. Under optimized conditions, the novel sensor displayed outstanding electrochemical reactivity towards the electro-oxidation of quinoline. The linear range was fixed between 0.0004 and 1.0 μM, with a limit of detection (LOD) of 3.75 nM. The fabricated electrode exhibited high stability with excellent sensitivity and selectivity, specifically attributable to the salient characteristics of AuNPs, CTSNPs, and MWCNTs and the synergistic inter-relationship between them. The newly developed electrode was tested in the field. The Ipa increased with an increase in the amount of quinoline solution added, and the peak potential deviated minimally, depicting the real capability of the newly fabricated electrode.